A Woman with a Long History of Smoking and a Debilitating Dry Cough - N. D. Potskhverashvili; N. I. Kokina; E. L. Bueverova; O. Yu. Zolnikova; A. S. Cherenda; V. A. Morozova; M. V. Feldsherov; A. P. Kiryukhin; P. V. Pavlov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present a clinical case of colorectal cancer in a woman with a long history of smoking and a leading complaint of dry cough.Key points. A 56-year-old patient with a long history of smoking was hospitalized in the pulmonology department of the clinic with a leading complaint of a constant debilitating dry cough during the day, not amenable to the action of drugs, as well as general weakness, sweating and weight loss by 2 kg in 3 months. The examination revealed a moderately differentiated adenocarcinoma of the hepatic bend of the colon with generalized lymphadenopathy and metastatic lung damage, iron deficiency anemia. Surgical treatment was performed at the Sechenov University surgical hospital: right-sided hemicolectomy with D2 lymph dissection (removal of epicolic, paracolic, mesocolic lymph nodes); adjuvant chemotherapy was prescribed. The patient is under the supervision of an oncologist and a coloproctologist.Conclusion. A clinical case of colorectal cancer in a woman with a long history of tobacco smoking and extra-intestinal symptoms is presented, demonstrating the need for cancer caution in relation to patients older than 50 years with iron deficiency anemia and lymphadenopathy. The timeliness of the diagnosis of a malignant neoplasm by primary care physicians is determined by the careful identification of cancer risk factors of this localization and the targeted search for “symptoms of anxiety”, upon detection of which endoscopic, radiation and morphological examination is necessary.